Body-biased VCO tunes 12 to 16 GHz - Moghavvemi, M.; Ameri Mahabadi, H.; Attaran, A. (2011)
This body-biased voltage-controlled oscillator provides reasonably good phase-noise performance over a broad tuning range with relatively low power consumption and low jitter timing noise in the time domain.